2016
DOI: 10.1016/j.acalib.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

ARL Libraries and Research: Correlates of Grant Funding

Abstract: While providing the resources and tools that make advanced research possible is a primary mission of academic libraries at large research universities, many other elements also contribute to the success of the research enterprise, such as institutional funding, staffing, labs, and equipment. This study focuses on U.S. members of the Association for Research Libraries (ARL). Research success is measured by the total grant funding received by the University, creating an ordered set of categories. Combining data … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Womack 159 , identifica que la biblioteca y sus recursos son indispensables en los procesos investigativos, de esta manera, analiza el impacto de la biblioteca con respecto a las investigaciones realizadas en la universidad. Sánchez-Barrioluengo 160 , menciona la importancia de la docencia e investigación en beneficio de la sociedad, dicho de otro modo, se refiere a las investigaciones que generen impacto social haciendo alusión a la tercera misión de la universidad.…”
Section: Docencia La Docencia Como Una Función Que Sustenta El Proyectounclassified
“…Womack 159 , identifica que la biblioteca y sus recursos son indispensables en los procesos investigativos, de esta manera, analiza el impacto de la biblioteca con respecto a las investigaciones realizadas en la universidad. Sánchez-Barrioluengo 160 , menciona la importancia de la docencia e investigación en beneficio de la sociedad, dicho de otro modo, se refiere a las investigaciones que generen impacto social haciendo alusión a la tercera misión de la universidad.…”
Section: Docencia La Docencia Como Una Función Que Sustenta El Proyectounclassified
“…28 In a methodologically sophisticated study, employing linear and logistic regression and a cumulative logit model, Womack used data from ARL, IPEDS, and the NSF's National Center for Science and Engineering Statistics (NCSES) to evaluate library impacts on grant funding received by 99 ARL-affiliated universities. 29 Another study analyzed the relationship between academic libraries and faculty research productivity at 103 ARL-affiliated universities; no effects were found. 30 At least one study examined academic library impacts on undergraduate students' development of critical thinking skills.…”
Section: Multi-institution Studiesmentioning
confidence: 99%
“…Therefore, libraries need to constantly work to increase the quality of their services in such a competitive environment (Somaratna and Peiris, 2011). According to Shoeb (2011) and Womack (2016), another challenge is the rising necessity for academic libraries effectiveness to prove their worth in order to get funding. Quantitative measurements of the library services, including the number of users, degree of service quality and the frequency with which services are used may be sought by funding institutions.…”
Section: Introductionmentioning
confidence: 99%